2007
DOI: 10.1530/rep-06-0092
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and interferon tau regulate RSAD2 and IFIH1 expression in the ovine uterus

Abstract: Radical S-adenosyl methionine domain containing 2 (RSAD2) encodes a cytoplasmic antiviral protein induced by interferons (IFN). Interferon-induced with helicase C domain 1 (IFIH1) is a RNA helicase involved in innate immune defense against viruses, growth suppression, and apoptosis. Interferon tau (IFNT), a Type I IFN produced by the peri-implantation ruminant conceptus, acts on the uterine endometrium to signal pregnancy recognition and promote receptivity to implantation. Transcriptional profiling identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 61 publications
1
58
0
Order By: Relevance
“…During early pregnancy or following intrauterine IFN treatment, the expression of the majority of progesterone-independent ISGs such as RSAD2 (radical S-adenosyl methionine domain containing 2) and IFIH1 (interferon-induced with helicase C domain 1) was increased in endometrial stroma, glands and immune cells but not in the luminal epithelium. In contrast, some non-classical ISGs such as LGALS15 (galectin 15), CTSL (cathespin L) and CST3 (cystatin C), which require progesterone priming, were predominantly expressed in the endometrial luminal epithelium and superficial glandular epithelium (Song et al 2007, Bazer et al 2008.…”
Section: Discussionmentioning
confidence: 96%
“…During early pregnancy or following intrauterine IFN treatment, the expression of the majority of progesterone-independent ISGs such as RSAD2 (radical S-adenosyl methionine domain containing 2) and IFIH1 (interferon-induced with helicase C domain 1) was increased in endometrial stroma, glands and immune cells but not in the luminal epithelium. In contrast, some non-classical ISGs such as LGALS15 (galectin 15), CTSL (cathespin L) and CST3 (cystatin C), which require progesterone priming, were predominantly expressed in the endometrial luminal epithelium and superficial glandular epithelium (Song et al 2007, Bazer et al 2008.…”
Section: Discussionmentioning
confidence: 96%
“…As illustrated in Figs 1-3 and summarized in Supplementary Table 1, numerous ISGs are induced or stimulated in the endometrium during conceptus elongation in both cattle and sheep. Curiously, in vivo studies revealed that many classical ISGs (b-2-microglobulin (B2M), guanylate-binding protein 2 (GBP2), interferon, a-inducible protein 27 (IFI27), interferon-induced protein with tetratricopeptide repeats 1 (IFIT1), interferonstimulated gene 15 (ISG15), IRF9, MHC class I polypeptide (MIC), 2 0 ,5 0 -oligoadenylate synthetase (OAS), radical S-adenosyl methionine domain containing 2 (RSAD2), STAT1, and STAT2) are not induced or upregulated by IFNT in endometrial LE of the ovine uterus (Johnson et al 1999b, Kim et al 2003, Song et al 2007). This finding was initially surprising, because all endometrial cell types express IFNAR1 (interferon (a, b, and u) receptor 1) and IFNAR2 subunits of the common type I IFNAR (Rosenfeld et al 2002).…”
Section: Ifnt and The Jak-stat-irf Pathwaymentioning
confidence: 99%
“…CX proteins were prepared for intrauterine injection as described previously (Spencer et al 1995). This regimen of P4 and roIFNT mimics the effects of P4 from the CL and IFNT from the conceptus on endometrial expression of hormone receptors and ISGs during early pregnancy in sheep (Song et al 2005(Song et al , 2006a(Song et al , 2007(Song et al , 2008a(Song et al , 2008b. All ewes were hysterectomized on day 17, and uteri processed as described for study 1.…”
Section: Studymentioning
confidence: 99%